Country Partnership Framework for the Republic of Niger for the Period of FY18-FY22 - World Bank Group (World Bank, Washington, DC, 2018)
This Country Partnership Framework (CPF) presents the World Bank Group (WBG) program for Niger for the period FY18-FY22. The CPF comes at an opportune moment as an exceptional volume of resources is now available to Niger, allowing the WBG to intensify and deepen its engagement in Niger. It will succeed the FY13-FY16 Country Partnership Strategy (CPS), and is aligned with the second Plan for Economic and Social Development (Plan de Développement Economique et Social - PDES) prepared by the Government of Niger (GoN) within the context of its Vision 2035. The CPF draws on a comprehensive Systematic Country Diagnostic (SCD)2 completed in FY17, which identified growth constraints and opportunities to achieving the World Bank’s Twin Goals of eliminating poverty and fostering shared prosperity in a socially and environmentally sustainable way. It also reflects the GoN’s commitment to the Sustainable Development Goals (SDGs) and its responsibilities and priorities around climate change mitigation and adaptation. The overarching goal of the CPF is to help safeguard and accelerate Niger’s economic and social development, by tackling growth constraints, unsustainable population growth and other fundamental (and emerging) drivers of fragility. In the short term, and within this overarching goal, the FY18-FY22 CPF will not only focus on boosting rural productivity and incomes, and strengthening human capital and governance, but also on empowering women and girls, a key strategy to reverse Niger’s record high levels of fertility and population growth. In the medium-term, reduced demographic pressures are expected to unleash women’s economic potential and free up public resources for improving basic service delivery, which in turn will enable further empowerment of women and girls in a self-sustaining virtuous circle. The CPF will also address fragility, conflict and violence (FCV) risks by supporting Niger’s response to existing crises and by helping to reduce rising tensions. This will require targeting resources to the most fragile and crisis-affected regions and directly addressing other drivers of conflict and fragility, such as youth disenfranchisement, grievances over allocation of government resources, and competition for scarce natural resources. Strengthening institutions will be critical to manage these risks and support social cohesion. The CPF draws on the combined contribution of the WBG including renewed efforts by the International Finance Corporation (IFC) and Multilateral Investment Guarantee Agency (MIGA) to derisk private investment in Niger. This CPF sets out a strategy for achieving a crucial change of trajectory financed by a doubling of resources relative to the previous CPS. The program draws on new sources of financing available under the International Development Association (IDA), including enhanced country allocation with additional resources from the Risk Mitigation Regime (RMR)3, and potential access to the Refugees Sub-Window, the Regional Integration Window, and other IDA windows. Total IDA resources available in IDA18 could be over US$1 billion, which represents an unprecedented opportunity to upgrade and expand the scope of the WBG’s assistance in Niger.